Implementing long-lasting insecticide netting as a tool for diversifying integrated pest management programs of stored product insects - Wilkins, Rachel Victoria (Kansas State University, 2020)
Stored products represent an enormous economic output, but insects regularly immigrate into these stored products from the surrounding landscape throughout the post-harvest supply chain, feed on these products, and cause extensive economic losses. Integrated pest management (IPM) holistically combines multiple management techniques to control an insect within a system. A key component of an IPM program is prevention. Deploying effective prevention strategies is a proactive approach to managing insects prior to them contacting and infesting food facilities and products. Long-lasting insecticide netting (LLIN), which usually contains an incorporated pyrethroid, has been used as part of a strategy to reduce the spread of malaria in tropical regions since the 1990’s, and has only recently been considered for its application in pre- and post-harvest agricultural contexts as a preventative IPM tool. The goals of this thesis were to evaluate the behavioral effects of LLIN (0.4% deltamethrin) on the movement and dispersal ability of three stored product insect species: Tribolium castaneum, Rhyzopertha dominica, and Trogoderma variabile in laboratory tests. Additionally, the efficacy of LLIN in semi-field, release-recapture assays was evaluated by deploying the netting in pilot-scale warehouses alone or within attract-and-kill (AK) traps to intercept insects immigrating into food facilities and attempting to enter commodities. Within the parameters of this thesis, LLIN was found to significantly reduce distance traveled and velocity of all three focal species. The ability of the insects to disperse to a novel food resource after exposure to LLIN was significantly reduced as well. Immature stages of T. castaneum and T. variabile were also significantly reduced in their movement and dispersal ability after exposure to the netting. Both life stages showed reductions in mobility after short exposure times to the netting, and these effects were long-lasting. In the semi-field experiments, pilot-scale warehouses that deployed LLIN had significantly fewer infestations and subsequent progeny production inside their commodities compared to warehouses without LLIN. Among the three tested methods of netting deployment, the efficacy of each deployment type was similarly effective. Finally, the efficacy of LLIN was evaluated in combination with another IPM tool, AK traps, which contained a small amount of grain and a commercial lure, all confined within two pieces of LLIN as the kill mechanism. Deploying these tools, alone or together, resulted in significant numbers of affected individuals recaptured inside the warehouse, yet outside of the commodity. Overall, LLIN is a promising tool for diversifying prevention tactics of stored product IPM. Future work should evaluate the performance of the netting in commercial food facilities and with other IPM tactics to create novel management strategies and continue evolving alongside these post-harvest pests.
Keywords: Long-lasting insecticide netting; Integrated pest management; Post-harvest; Tribolium castaneum; Rhyzopertha dominica; Trogoderma variabile